Stabilization of rice bran using a continuous microwave oven - Pongrat, Pattarabhorn; Songsermpong, Sirichai (Agriculture and Natural Resources, 2019)
The effects of continuous microwave heating and storage temperature on free fatty acids (FFA) contents, peroxide values (PV) and 2-thiobarbituric acid values (TBA) in rice bran stabilization were examined. Raw rice bran (RRB) was adjusted to 21% moisture content on a wet basis and heated in a continuous microwave oven at 6,400 W and 2,450 MHz for 15.75 min. Then, it was packed in zipper-topped bags and stored at 4°C and 25°C for 16 wk. After 16 wk, the FFA contents of the RRB stored at 4°C and 25°C increased from 4.42% to 35.78% and 53.24%, respectively. Overall, there was no significant change in the continuous microwaved rice bran (MWRB) during storage. The PV and TBA values of RRB stored at 4°C and 25°C significantly increased and were higher than for MWRB. The results showed that a hydrolytic reaction and oxidative rancidity of rice bran can be prevented using continuous microwave heating. The heating affected the hydrolytic reaction and oxidative rancidity when the solutions were packed in zipper-topped bags and stored at 4°C for up to 16 wk.